Implementation of Social Media Marketing for MSMEs - Muji Raharjo (International Journal of Education, Information Technology, and Others, 2020)
Social media marketing is a variety of marketing tools that can be used easily and inexpensively, when compared to other marketing tools. With lower costs than other marketing tools, MSMEs tend to be suitable for using social media marketing methods to introduce their products, build relationships with customers and strengthen their brands. In fact, only 30% of businesses in Indonesia use digital instruments, so more research is needed to explore the perspective of the company, especially in understanding the barriers or obstacles in the use of social media marketing. The purpose of this research is to describe the concept of social media marketing, the use of social media as a means of promotion for MSMEs, the impacts and challenges faced by MSMEs in the use of social media. Planning to use social media as a competitive marketing tool requires message content that can grab the attention of customers. In addition, sincerity, attention and quick response are also needed in communicating with target customers. Challenges in the use of social media marketing by MSMEs, which include internal and external factors, are things that must be faced and anticipated in order to achieve success in social media marketing